Efektifitas Terapi Psikoedukasi terhadap Peningkatan Tumbuh Kembang Anak - Siti Haryani; Ummu Muntamah; Ana Puji Astuti ((JKG) Jurnal Keperawatan Global, 2020)
Background: The Background from the research is a nurse as part of health services to contribute in realizing from the program to improve the quality of children’s development through efforts to psychological services of children. This is a nurse as a concelor.This research has purpose to describe about effectiveness of psychoeduation to development child. Methods: This type of correlation research, research methods with action research, the sampling techniques is using total sampling technique, the number of samples used all kindergarten students Nurul Izzah, statistical tests using Wilcoxon. This data has analyzed with descriptive analysis dan pre test dan post test design use SPSS (Statistical Packages for Social Sciences). Second step is implementation of psychoeducation to the parents, the instrument used is to use the KPSP question guideObject of this reearch is children and parents. This metode is survey. This resesarch was done 2 step. First step was done pre test of children’s development use by KPSP. Results: The result is psychoeduation very strong influences on children’s development p=0.000 (p<0.05). Conclusion: Psychoeducation therapy will help the development of children according to age.Research recommendations are to support the growth and development of children, schools can provide education and training on psychoeducation by involving teachers and parents.